2008
DOI: 10.1590/s0100-84042008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura genética populacional de Copaifera langsdorffii Desf. (Leguminosae - Caesalpinioideae) em fragmentos florestais no Pontal do Paranapanema, SP, Brasil

Abstract: -(Population genetic structure of Copaifera langsdorffii Desf. (Leguminosae -Caesalpinioideae) in forest fragments in "Pontal do Paranapanema", SP, Brazil). The "Pontal do Paranapanema" is the most recently deforested region of the state of São Paulo in Brazil. The effects of forest fragmentation on the population genetic structure of Copaifera langsdorffii Desf. were evaluated by genotyping with six microsatellite loci at least 30 adult and 30 sapling individuals of three populations in "Pontal do Paranapanem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
2
14
0
4
Order By: Relevance
“…This pattern of genetic structure is expected for tree species with efficient mechanisms of gene flow, such as tropical tree species that are pollinated by animals and have seed dispersal. Previous studies with C. langsdorffii observed a similar pattern with low genetic differentiation among populations (Carvalho and Oliveira, 2004;Martins et al, 2008). The observed low genetic differentiation between the populations indicates the lack of isolation and intense gene flow between the populations, which homogenizes its genetic diversity.…”
Section: Discussionsupporting
confidence: 70%
“…This pattern of genetic structure is expected for tree species with efficient mechanisms of gene flow, such as tropical tree species that are pollinated by animals and have seed dispersal. Previous studies with C. langsdorffii observed a similar pattern with low genetic differentiation among populations (Carvalho and Oliveira, 2004;Martins et al, 2008). The observed low genetic differentiation between the populations indicates the lack of isolation and intense gene flow between the populations, which homogenizes its genetic diversity.…”
Section: Discussionsupporting
confidence: 70%
“…The high genetic divergence observed between the populations of Santa Genebra and Tietê is most likely related to the low gene flow resulting from forest fragmentation (Frankham et al, 2008). Similar results were found for the Copaíba tree (Copaifera langsdorffii) by Martins et al (2008), whereby it was suggested that forest fragmentation restricts gene flow between populations of these species, possibly due difficulty in pollinator movement. The genetic isolation may also be related to the high number of private alleles found in this study (Karasawa, 2005).…”
Section: Resultssupporting
confidence: 71%
“…Null alleles have been found in more than 25 % of the microsatellite loci, reaching frequencies over 15 % (Jarne and Lagoda, 1996) and observed in other plants such as Allium cepa L. cultivars (Santos et al, 2010) and Copaifera langsdorffii Desf. (Martins et al, 2008), among others. Null alleles may be due mainly to the lack of a sequence for the initiatior annealing, due to point mutations.…”
Section: Resultsmentioning
confidence: 98%
“…In T. pratense, Dias et al (2008), also using SSR found high intrapopulational variability in a core collection of red clover (T. pratense), number of alleles per locus ranging from seven to 12. Null alleles, those alleles that are consistently not amplified (Martins et al, 2008) were observed in SSR ats 070, TM0133 and TM0256 (Table 2). Null alleles have been found in more than 25 % of the microsatellite loci, reaching frequencies over 15 % (Jarne and Lagoda, 1996) and observed in other plants such as Allium cepa L. cultivars (Santos et al, 2010) and Copaifera langsdorffii Desf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation